A T-acute lymphoblastic leukemia in children with CD 117 expression: a case report - Komang Juwita Endrawati (Bali Medical Journal, 2019)
Background: Leukemia is a group of clonal disorders originating from single cells with genetic changes in the bone marrow or peripheral lymphoid tissue. Acute T-cell lymphoblastic leukemia is estimated to be 12-15% of ALL cases. Immunotyping examination is essential in establishing the diagnosis of T-ALL, CD 1a, CD 2, CD 3 (membranous and cytoplasm), CD 4, CD 5, CD 7, and CD 8 as T- cell antigen markers. CD 33, CD 117, CD 34 and CD 56 are a myeloid-related antigen. The occurrence of co-expression of T cell markers with markers myeloid is infrequent. This study aimed to report cases of T- Acute Lymphoblastic Leukemia (ALL) in children with CD 117 expression. Case description: A-13 years boy had a fever and bruising on the skin one year ago. Physical examination found a blood pressures 150/70 mmHg , axillary temperature 37.8 ° C, right and left enlargement of the glands of the neck and inguinal, enlarged liver and petechiae in both lower extremities. Complete blood tests showed leukocytosis, anemia, and thrombocytopenia. Edge blood smear suggests the presence of cigar cells, target cells and lymphoblasts > 50%. Bone marrow aspiration smear revealed lymphoblast >30% and concludes an ALL (L2). Immunophenotyping examination found CD 3, CD 5, CD 117 positively supported T-ALL with co-expression of CD 117. During treatment, the patient experienced seizures due to spontaneous intracerebral bleeding that caused the patient to die. Conclusion: The case of a 13-year-old boy suffering from T-ALL (L2) with co-expression of CD 117 had a poor prognosis.